The effect of audit tenure, audit rotation, accounting firm size, and client’s company size on audit quality - Desi Frida Priyanti; Nurul Hasanah Uswati Dewi (The Indonesian Accounting Review, 2019)
This study aimed to examine the effect of audit tenure, audit rotation, public accounting firm size, and client’s company size on audit quality. Audit quality in this study is peroxided by earnings quality which is measured by the level of discretionary accruals of modified jones model, while audit tenure is measured by counting the year in which the same auditors have made work engagement with the auditee. Audit rotation and public accounting firm size are measured by using dummy variable, while client’s company size is measured by using the growth of total assets. The population in this study consists of public companies, especially the telecommunications and retail sectors service companies listed in Indonesia Stock Exchange in the period 2012-2017. Sampling technique used is purposive sampling method. The total of the sample is 30 companies. After data observation, there are 73 samples included as outlier and should be excluded from samples of observation. So, the final data used are 107 data. Multiple linear regressions analysis is used as analysis technique. The empirical results of this study show that audit tenure and public accounting firm size have no effect on audit quality; audit rotation has negative and significant effect on audit quality; and client’s company size has positive and significant effecton audit quality.